The use of connectors: corpus-based error analysis of Chinese speaking learners of Spanish - Yang, Qin (2023)
The paper aims to discover the frequent and specific errors of Chinese-speaking learners of Spanish as a foreign language when using discourse markers in written texts. For this purpose, the methodological foundations of the corpus analysis of learners developed by Ramos (2016) are considered, as well as Corder's (1971) error analysis. The results quantify the errors and present a classification of these, while offering a beginning explanation of the mechanisms that lead to their production. In this way, the results can be useful for anticipating the difficulties encountered by learners, as well as for designing a didactic implementation and producing material adapted to them.